Analysis of Surgical Resection of Non-Melanoma Skin Cancer in The Head and Neck of Elderly Population in a Public Hospital of São Paulo - Marinho Vidigal, Maria Luiza; Godoi Ignáciz, Nathalia; Zafer Merhi, Mahmoud; Carrijo Costa, Pamela; Barão da Silva, Diego; Bartolomei de Siqueira Corradi, Matheus (International Journal of Clinical Research, 2022)
Introduction: Skin cancer is among the most frequent neoplasms worldwide. It is divided into two major groups: non-melanoma skin cancer (NMSC) and melanoma skin cancer (MSC), with NMSC still classified into several subtypes, with the most prevalent being basal cell carcinoma subtype (BCC), followed by squamous cell carcinoma (SCC). Although NMSC does not present high mortality rates, it can involve high morbidity on the functional, aesthetic, and emotional levels. There is a divergence in the literature regarding decision-making in the cases of elderly (patients above 65 years of age) and super elderly patients (starting at 80 years of age). Objectives: This study aims to: 1. Identify the complications of surgical resection of the NMSC of the face and neck in the elderly population. 2. Demonstrate that surgical resection can be used as a therapeutic option in the elderly population without a significantly higher risk of morbidities. Method: This is a transversal, retrospective single-center study of quantitative nature. After the approval of the Research Ethics Committees, analysis was performed on the electronic records of 34 patients who underwent surgery at the Carapicuíba General Hospital between August 2017 and November 2019. The descriptive analysis of the results was performed employing absolute and relative frequency of the qualitative variables; mean and standard deviation were used for the quantitative variables. Analysis of group differences was done through the Fisher's Exact, Student's, or Mann-Whitney T-tests, to evaluate the factors associated with the complications of the procedure. Results: The results showed a mean age of 85.1 years; higher prevalence in females (61.8%); higher prevalence of BCC (76.5%); higher involvement in the nasal (23.5%), periauricular (23.5%), and malar regions (17.7%); hypertension (55.9%), and diabetes mellitus (35.3%) as the main comorbidities; 8 (23.5%) patients had post-surgical complications, and 0 patients had intraoperative complications. Conclusion: It was concluded that surgical resection was a good therapeutic method for the patients approached in the study. It is suggested that the therapeutic choice should be individualized, with the evaluation of the patient as a whole and taking into account aspects other than age group and comorbidities. Moreover, it is necessary to develop new studies and clinical trials with a more significant sample.